180. SINGLE-PORT MEDIASTINOSCOPIC LYMPHADENECTOMY IN THE UPPER AND MIDDLE MEDIASTINUM USING CONTINUOUS INTRAOPERATIVE NERVE MONITORING. (24th September 2022) - Fujiwara, Hitoshi; Shiozaki, Atsushi; Konishi, Hirotaka; Kubota, Takeshi; Ohashi, Takuma; Otsuji, Eigo
Abstract: The left cervical approach with single-port mediastinoscopy is essential for radical esophagectomy without thoracotomy for esophageal cancer, which provides excellent visibility and handling along the esophagus to achieve radical lymph nodes (LNs) dissection in the upper and middle mediastinum. However, the transcervical procedure dissecting along the recurrent laryngeal nerve (RLN) requires careful use of both energy device for dissection and forceps for surgical field expansion to minimize the risk of RLN palsy. Using the left cervical approach, the LNs along the left RLN and tracheal bifurcation (subcarinal and bilateral main bronchial LNs) were dissected en bloc with the esophagus. The LNs along the right RLN were basically dissected through a right cervical incision under direct vision or dissected with the left cervical approach if visible. Intraoperative nerve monitoring (IONM) with NIM Response 3.0 was introduced to minimize the risk of RLN palsy. Continuous and intermittent IONMswere used for the left and right cervical procedures, respectively. Until March 2019, 175 patients underwent transmediastinal esophagectomy. Squamous cell carcinoma was predominant (93.7%). The upper and middle thoracic tumors were the most frequent (65.7%). Since IONM introduction, RLN palsy (grade I or more, CD classification) was significantly reduced. Without IONM (n = 106), the left RLN palsy was observed in 35.9%, while was in 13.6% with IONM (n = 66). In addition, the bilateral RLNs palsy was 14.2% without IONM, while was reduced to 3.0% with IONM. IONM is useful to reduce RLN palsy in transmediastinal esophagectomy. Especially, continuous IONM, which provides a real-time information on the risk procedure of RLN injury, is effective in preventing RLN palsy. The left cervical procedure with continuous IONM will be shown in movie.